Inland Waterway Transportation as an Indicator of Livability in the City of Kochi - Havila Rose K (Calibrating Urban Livability in the Global South, 2024)
This paper explores the impact of inland waterway transportation on the livability of Kochi, a major city in Kerala, India, with a focus on the convenience of the public in utilizing this mode of transport. Urbanization in India has led to increasing urban populations and associated challenges, such as informal settlements and pollution, which affect the quality of life and livability in cities. Livability, defined as the quality that makes a place suitable for living, emphasizes the importance of accessible and reliable transportation as a critical component. The study concentrates on Kochi, known for its significant reliance on public transport, including buses and ferries. The research aims to analyze the convenience of using the inland waterway transportation system in Kochi and its implications for city livability. The methodology involves site visits and observations with a specific focus on the Ernakulam Ferry station and Fort Kochi area to identify major issues, particularly the first and last-mile connectivity challenges. Findings indicate that despite the economic and environmental benefits of waterway transportation, the lack of convenient first and last-mile connectivity, along with poor pedestrian infrastructure and limited disabled access, hinders its usage. The paper suggests several improvements, such as the introduction of feeder bus services, relocation of bus stops closer to ferry stations, enhancement of pedestrian pathways, and the implementation of shared auto systems, to improve overall accessibility and encourage the use of inland waterway transportation. These measures aim to enhance Kochi’s livability by providing an interconnected public transportation system that is convenient, comfortable, and economical for its residents.